Tandha’ Dance in Sumenep: Dynamics and Shifting Islamic Values in Local Cultural Representation - Yusro, Lailatul; Khairul Umam (KARSA Journal of Social and Islamic Culture, 2023)
Tandha’ is a local art in Madura, not least in the Sumenep district, which was once used as a medium for da'wah, so there are many Islamic values in it. However, over time, the Islamic value is replaced by the materialistic value in the practice of tandha' itself, so much so that its existence even causes controversy in the community. This shift has also changed the characteristics of tandha' as a local art in Sumenep. This study aims to look at tandha’ in its original form, which is full of Islamic values and is very distinctive, and how the shift occurred and what aspects have changed in tandha.' Looking at all of this, we may find a middle ground for the controversy over tandha' itself in the community. As a local art form, it must be preserved and kept pure. This research attempts to answer this question using a descriptive qualitative method with data from field studies and previous research literature studies. The results of this research find a shift in tandha’ occurred since the space for tandha’ began to expand from the palace to the lives of the general public and also cannot be separated from the dark history of tandha’, which later became an economic support so that the underlying Islamic value changed to materialistic values and it also slowly changed the composition in tandha’ itself to threaten Islamic values and threaten Madurese art in it. Therefore, instead of arguing pros and cons, the government, artists, and religionists should start working together to restore tandha’ to its authenticity.